HUBUNGAN KEKUATAN OTOT LENGAN DAN KEKUATAN OTOT PERUT DENGAN KEMAMPUAN MELAKUKAN SIKAP LILIN PADA SENAM LANTAI SISWA KELAS VIII SMPN 4 PRAYA TENGAH TAHUN PELAJARAN 2015/2016 - Rindawan Rindawan; Muhamad Satria Mulyajaya (Jurnal Ilmiah Mandala Education (JIME), 2016)
The problem of this research was the lack of comprehension in arm mucles power and balance to improve the cart wheel ability. The objective of this class action research was to know whether the correlation of arm muscles power and balance to improve the cart wheel ability in floor exercise at eighth grades student of SMPN 1 Lopok Sumbawa in 2015/2016 academic year. The sample of this research was 20 students which are they tested the arm muscles power and balance and also their the cart wheel ability. This research used quantitave approach. The research design used multiple correlation design. The data collection in this study used research instruments which are 30 second push-ups test, once trial strock stand test and once trial the cart wheel ability test. The result of this research showed that there was a correlation of arm muscles power toward the cart wheel ability with 5% significant level. It also showed that there was a correlation of arm muscles balance toward the cart wheel ability with 5% significant level. The final result showed that there was a correlation of arm muscles power and balance toward the cart wheel ability with 5% significant level. It could be concluded that there was a correlation of arm muscles power and balance to improve the cart wheel ability in floor exercise at eighth grades student of SMPN 1 Lopok Sumbawa in 2015/2016 academic year.